Antiviral Activity of Liposomes Containing Natural Compounds Against CHIKV - Calmon, Marília Freitas [UNESP]; Gusmão, Luiza Araújo; Ruiz, Thalles Fernando Rocha; Campos, Guilherme Rodrigues Fernandes; Ayusso, Gabriela Miranda; Carvalho, Tamara; do Vale Francisco Bortolato, Isabella [UNESP]; Conceição, Pâmela Joyce Previdelli [UNESP]; Taboga, Sebastião Roberto [UNESP]; Jardim, Ana Carolina Gomes [UNESP]; Merits, Andres; Rahal, Paula [UNESP]; et al. (MDPI, 2025)
Background/Objectives: Chikungunya virus (CHIKV), a mosquito-borne single-stranded RNA virus belonging to the genus Alphavirus (family Togaviridae), causes large-scale outbreaks. However, no specific treatment for CHIKV infections is currently available. Berberine and emodin are plant-derived compounds with anti-CHIKV activities. This study aimed to evaluate the antiviral efficacy of liposomes containing berberine (LB) or emodin (LE) against CHIKV in vitro, since nanocarriers incorporating zwitterionic polymers are known to enhance the biostability, biocompatibility, and therapeutic efficacy of drug candidates. Methods: Liposomes were synthesized and characterized, and cell viability was assessed to determine appropriate concentrations for subsequent assays. Confocal microscopy, antiviral assays, and western blotting were performed in BHK-21 and Huh7 cells. Results: In BHK-21 and Huh7 cells, LB and LE were well tolerated at concentrations of 5 and 10 µM, respectively. In both cell types, liposomes were internalized; LE was predominantly localized in the cytoplasm, whereas LB was also detected in the nucleus. EGCG, used as a standard drug against CHIKV in antiviral assays, exhibited virucidal activity and inhibited RNA replication and multiple stages of the CHIKV replication cycle in BHK-21 and Huh7 cells. Both the nanoformulations and EGCG consistently suppressed the expression of CHIKV replicase and virion proteins. Conclusions: These findings highlight the potential of berberine- and emodin-loaded liposomes as antiviral agents against CHIKV infection.